2022
DOI: 10.1108/intr-06-2021-0348
|View full text |Cite
|
Sign up to set email alerts
|

The past and beyond of mobile payment research: a development of the mobile payment framework

Abstract: PurposeMobile payment (m-payment) has existed for over 25 years; however, there is no standard framework to guide scholars and practitioners in advancing m-payment research in the digital accelerated era. With this, this study aims to develop an m-payment framework and to analyse the evolution of m-payment research from 1997 to 2021. These were achieved by identifying the motor themes, basic and transversal themes, the emerging/declining themes and the highly developed but isolated themes. In addition, the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…It can be confirmed from a recent study which has analyzed and developed the evolution of mobile payment research from 1997 to 2021 [5]. According to their study, from the perspective of behavior, mobile payment can be studied based on various customer behavior factors.…”
Section: Introductionmentioning
confidence: 88%
“…It can be confirmed from a recent study which has analyzed and developed the evolution of mobile payment research from 1997 to 2021 [5]. According to their study, from the perspective of behavior, mobile payment can be studied based on various customer behavior factors.…”
Section: Introductionmentioning
confidence: 88%
“…The literature review on m-payment research revealed that the TAM was the most popular approach to understanding the key drivers of m-payment use (Dahlberg et al. , 2015; Leong et al. , 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Most of the NFC m-payment literature adopted the theory of technology acceptance (TAM) to study customer attitudes and intentions to use NFC m-payment (Leong et al, 2022). NFC mpayment for customer loyalty in retail 347…”
Section: Introductionmentioning
confidence: 99%
“…, 2016). In fact, the adoption of digital payment methods (DPMs) has increased worldwide, and cash usage has further decreased due to the COVID-19 pandemic, forcing a move from traditional to digital services (Leong et al. , 2022; Santo and Marques, 2022).…”
Section: Introductionmentioning
confidence: 99%